Effect of ZnGeP₂ annealing in Zn vapor on the laser spectrum - Patskun, I.I.; Rybalko, A.V. (Functional Materials, 2005)
The work is devoted to experimental investigation of the band structure, deep local centers and complexes as well as of generation/recombination processes in the ZnGeP₂ semiconductor crystal. The crystals grown by Bridgeman technique, annealed in Zn vapor and unannealed were studied. The dynamics of the defect structure change in the ZnGeP₂ crystal due to annealing in Zn vapor has been considered as well as the presumable identification of impurity centers.